2000
DOI: 10.2307/3803250
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Success of Elk Following Disturbance by Humans during Calving Season

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 11 publications
2
58
0
Order By: Relevance
“…3). Disturbance at a specific site also was identified and, as with roads, was usually associated with breeding or rearing young (Foppen andReijnen 1994, Phillips andAlldredge 2000).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Disturbance at a specific site also was identified and, as with roads, was usually associated with breeding or rearing young (Foppen andReijnen 1994, Phillips andAlldredge 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Hayes et al (2002) reported that mortality of elk during hunting season increased when total road density increased. In addition, elk reproductive success has been shown to decrease following human disturbance to calving areas (Phillips and Alldredge 2000). Cole et al (1997) showed that road closures are successful in reducing the effects of habitat displacement and increasing elk survivorship.…”
Section: --------------Meters --------------mentioning
confidence: 99%
See 1 more Smart Citation
“…This brings with it the possibility of effects on the welfare and/or productivity of wildlife, in cases where disturbance alters behaviour patterns. Reduced calving rates in elk Cervus elaphus canadensis have been linked to human disturbance (Philips and Alldredge 2000), as have increased heart rates in sheep (MacArthur et al 1979(MacArthur et al , 1982 and birds (Weimerskirch et al 2002;Ackerman et al 2004;Ellenberg et al 2006) and increases in energy expenditure in a range of species (Speakman et al 1991;Staines and Scott 1994;Regel and Putz 1997;Stock and Hofeditz 1997;Wolfe et al 2000). Disturbance has also been shown to alter habitat use by wild ungulates (Gander and Ingold 1997;Jiang et al 2009;Jayakody 2005), with the potential for altering diet composition if the source of disturbance coincides with a particular habitat type.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we were unable to conclude the fawn's fate, although we believe it was killed. We did not inspect the area until the following morning because our work required repeated observations of Elk in this meadow (Phillips and Alldredge 2000) and our disturbance would have compromised that work.…”
mentioning
confidence: 99%